The Role of Core Competencies in Enhancing Operational Efficiency in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia - Adoe, Vera Selviana (Eastasouth Institute, 2025)
This study investigates the role of core competencies in improving operational efficiency within Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs contribute significantly to the national economy but often face challenges in resource limitations, productivity, and competitiveness. Core competencies, defined as unique combinations of skills, knowledge, and organizational capabilities, are considered strategic enablers of efficiency and sustainability. Using a quantitative approach, data were collected from 150 MSME owners and managers through a structured questionnaire based on a 5-point Likert scale. The data were analyzed using SPSS version 25, employing descriptive statistics, validity and reliability testing, correlation, and regression analysis. The findings show that core competencies have a significant positive effect on operational efficiency, with a correlation coefficient of 0.652 and an R² value of 0.425, indicating that 42.5% of operational efficiency variance can be explained by competencies. The results highlight the importance of innovation capability, resource management, and market responsiveness in driving efficiency. This study contributes to the Resource-Based View (RBV) literature in the context of MSMEs and provides practical implications for managers and policymakers to strengthen MSME competitiveness through competency development.